The Effect of Beginning Treatment With Fremanezumab on Headache and Associated Symptoms in the Randomized Phase 2 Study of High Frequency Episodic Migraine: Post‐Hoc Analyses on the First 3 Weeks of Treatment. Issue 3 (18th November 2018) - Silberstein, Stephen D.; Rapoport, Alan M.; Loupe, Pippa S.; Aycardi, Ernesto; McDonald, Mirna; Yang, Ronghua; Bigal, Marcelo E.
Abstract : Background: Migraine has a substantial impact on daily living, affecting productivity and quality of life for patients and their families. Patients frequently discontinue preventive medications in part because of a delay in headache and symptom relief due to the long dose titration procedures necessary for some migraine preventives. Objective: To evaluate the efficacy of fremanezumab, a selective monoclonal CGRP ligand antibody, during the first 3 weeks of therapy in patients with high‐frequency episodic migraine (HFEM) to relieve migraine headaches and associated symptoms and to reduce use of acute migraine medications. Methods: In a multicenter, randomized, double‐blind, placebo‐controlled, phase 2 study, patients with HFEM who met inclusion criteria and were 80% compliant with daily headache diary entry were randomized and treated once every 28 days for 3 months with either placebo or fremanezumab 225 or 675 mg. Compared to placebo, both doses of fremanezumab significantly reduced the primary endpoint of the HFEM study, change in the number of migraine days in month 3 relative to baseline. Herein, we performed post‐hoc analyses to assess the efficacy of each dose during the first 3 weeks of treatment to reduce migraine headache parameters, associated migraine symptoms, and the consumption of acute migraine medications. Results: The sample consisted of 297 study participants. Compared to placebo, decreases in migraine days were seen during the first week of therapy for both fremanezumab doses with least square mean (LSM) differences between fremanezumab 225 mg and placebo of −0.93 (95% CI: −1.36, −0.49) and between 675 mg dose and placebo of −1.02 (95% CI: −1.46, −0.58), both P  < .0001. This benefit was maintained through the second week of therapy for the 225 and 675 mg doses, respectively, (−0.76 (95% CI: −1.11, −0.40) P  < .0001, −.79 (95% CI: −1.15, −0.44) P  < .0001) and the third week of therapy (−0.64 (95% CI: −0.97, −0.30) P  = .0003 and −0.64 (95% CI: −0.98, −0.30) P  = .0003). Likewise in the first week, patients recorded reductions in associated migraine symptoms such as nausea, vomiting, photophobia, and phonophobia, which continued through weeks 2 and 3. There were also reductions in days with acute medication use to treat migraine for the 225 and 675 mg fremanezumab doses compared to placebo. In the first week, LSM differences between 225 mg and placebo were −1.02 (95% CI: −1.39, −0.64) and between 675 mg and placebo were −1.06 (95% CI: −1.39, −0.64) P  < .0001); for the second and third weeks (−1.01 (95% CI: −1.14, −0.55) P  < .0001; −.90 (95% CI: −1.04, −0.44) P  < .0001; −.91 (95% CI: −0.92, −0.34) P  < .0001; and −.83 (95% CI: −0.84, −0.26) P  = .0002), respectively. Conclusion: Fremanezumab treatment resulted in a rapid preventive response in patients with HFEM, with reductions seen in several headache parameters and migraine symptoms within the first week after therapy initiation and continuing during the second and third weeks. Patients also were able to rapidly reduce their use of acute medications to treat migraine attacks. The trial is registered at Clinicaltrials.gov as NCT02025556.